Rola rynku w kształtowaniu się zarządzania globalnego - Rewizorski, Marek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
This text reflects on the role of the global market, defined as the space where various relations between states and private entities take place. The following examples are provided in the case of the latter: private arbitration, rating agencies, International Standard Organisation, The Internet Corporation for Assigned Names and Numbers, and Codex Alimentarius Commission. The market is depicted in the context of a number of economic and financial phenomena constituting the contemporary face of globalization. The article also presents the diverging standpoints of researchers as concerns the role attributed to the market in global governance as the space of activities of non-state entities, especially considering the fact that – as a more and more vital holder of power exceeding that of state powers – private structures are acquiring broad autonomy within national and international law. Thereby, they become important regulators of jurisdiction and the international economy. From this perspective, globalization leads to the extension of the scope of rules regulating more and more fields of economic activity conducted beyond national borders. The further weakening of the role states have in relation to market powers and entities involved in a broad range of actions in economy, trade, and international finances is therefore plausible.